Pathogenic Landscape of Transboundary Zoonotic Diseases in the Mexico–US Border Along the Rio Grande - Esteve-Gassent, Maria Dolores; Pérez de León, Adalberto A.; Romero-Salas, Dora; Feria-Arroyo, Teresa P.; Patino, Ramiro; Castro-Arellano, Ivan; Gordillo-Pérez, Guadalupe; Auclair, Allan; Goolsby, John; Rodriguez-Vivas, Roger Ivan; Estrada-Franco, Jose Guillermo (Frontiers in Public Health, 2014)
Transboundary zoonotic diseases, several of which are vector borne, can maintain a dynamic focus, and have pathogens circulating in geographic regions encircling multiple geopolitical boundaries. Global change is intensifying transboundary problems including the spatial variation of the risk and incidence of zoonotic diseases. The complexity of these challenges can be greater in areas where rivers delineate international boundaries and encompass transitions between ecozones. The Rio Grande serves as a natural border between the US State of Texas and the Mexican States of Chihuahua, Coahuila, Nuevo León, and Tamaulipas. Not only millions of people live in this transboundary region but also a substantial movement of goods and people pass through it everyday. Moreover, it occurs over a region that functions as a corridor for animal migrations, and thus links the Neotropic and Nearctic biogeographic zones, with the latter being a known foci of zoonotic diseases. However, the pathogenic landscape of important zoonotic diseases in the south Texas-Mexico transboundary region remains to be fully understood. An international perspective on the interplay between disease systems, ecosystem processes, land use, and human behaviors is applied here to analyze landscape and spatial features of Venezuelan equine encephalitis, Hantavirus disease, Lyme Borreliosis, Leptospirosis, Bartonellosis, Chagas disease, human Babesiosis, and Leishmaniasis. Surveillance systems following the One Health approach with a regional perspective will help identifying opportunities to mitigate the health burden of those diseases on human and animal populations. It is proposed that the Mexico-US border, along the Rio Grande region be viewed as a continuum landscape where zoonotic pathogens circulate regardless of national borders.